2014
DOI: 10.1016/j.expneurol.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Where attention falls: Increased risk of falls from the converging impact of cortical cholinergic and midbrain dopamine loss on striatal function

Abstract: Falls are a major source of hospitalization, long-term institutionalization, and death in older adults and patients with Parkinson’s disease (PD). Limited attentional resources are a major risk factor for falls. In this review, we specify cognitive–behavioral mechanisms that produce falls and map these mechanisms onto a model of multi-system degeneration. Results from PET studies in PD fallers and findings from a recently developed animal model support the hypothesis that falls result from interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 190 publications
6
98
0
Order By: Relevance
“…These results help elucidate how variation in cholinergic function, independent of pathology, impacts individual differences in attentional function and fMRI measures of PFC activity. Additionally, this work may shed light on the risk and resiliency factors associated with suboptimal cholinergic function, a condition also associated with disorders such as schizophrenia (Demeter et al, 2013; Luck et al, 2012) and Parkinson’s disease (Kucinski et al, 2013; Sarter et al, 2014a). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results help elucidate how variation in cholinergic function, independent of pathology, impacts individual differences in attentional function and fMRI measures of PFC activity. Additionally, this work may shed light on the risk and resiliency factors associated with suboptimal cholinergic function, a condition also associated with disorders such as schizophrenia (Demeter et al, 2013; Luck et al, 2012) and Parkinson’s disease (Kucinski et al, 2013; Sarter et al, 2014a). …”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic projections from basal forebrain to prefrontal cortex (PFC) are necessary for attentional performance (Hasselmo and Sarter, 2011), and abnormalities in the cholinergic system are implicated in the attentional deficits associated with neurodegenerative and psychiatric disorders (Counts and Mufson, 2005; Mesulam, 2004; Mufson et al, 2000; Sarter et al, 2014a; Sarter et al, 2012; Xie and Guo, 2004). However, little is known about how non-pathologic variation of endogenous cholinergic signaling influences attention and modulates PFC function in humans.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that DT might influence higher cortical functions for a long period. Attentional deficits and risk of falls are strictly associated with an incapability of the patient to focus on motor/postural and cognitive tasks when they are combined (Yarnall et al, 2011;Sarter et al, 2014). DT, for its intrinsic characteristics, might train the subject to properly address such tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Postural instability constitutes a major risk factor for disability, poor quality of life and long-term hospitalization (Sarter et al, 2014). Dance Therapy (DT) is a promising form of neuro-rehabilitation in PD, combining highly task-specific motor and attentional solicitations.…”
Section: Introductionmentioning
confidence: 99%
“…The first possibility is that some variable affects both verbal memory and posture, while another variable affects visuomotor performance and gait/mobility. For instance, the neurotransmitter acetylcholine is thought to be important both for visuomotor processing (Sarter and Bruno, 1997; Naber et al, 2015) and for gait (Yarnall et al, 2011; Bohnen and Jahn, 2013; Sarter et al, 2015), while dopamine has been shown to be important for posture (Benninger et al, 2015) and episodic memory (Shohamy and Adcock, 2010), especially in older adults (Papenberg et al, 2014; Abdulrahman et al, 2015). Interestingly, dopamine is thought to be less available in men than in women, likely because of the influence of estrogen (Becker, 1999; Mozley et al, 2001; Staley et al, 2001; Jacobs and D’Esposito, 2011).…”
Section: Discussionmentioning
confidence: 99%